Glucose solution concentration detection using TE011 microwave resonant cavity. Issue 14 (22nd September 2018) - Li, Qiao; Xiao, Xia; Fu, Hao; Wang, Liang
ABSTRACT: In this paper, a glucose solution concentration measurement method is proposed based on microwave resonant cavity perturbation technique. The mathematical model of TE011 cylindrical resonator in terms of solution concentration is derived. The optimal geometry of cavity is determined by high frequency structure simulator. A brass cavity with a PVC capillary tube is produced in this study. A microwave measurement system consisting of resonator, waveguide and network analyzer is constructed to measure glucose concentrations from 70 to 150 mg/dl, using frequency range 7.539–7.546 GHz. Statistical results indicate that the resonant frequency of solution increases linearly as glucose concentration increases. Frequency shift slope (FSS) of experiment is in good accordance with the FSS of theoretical calculation, which shows the feasibility and accuracy of the method.